THE MEDIATING EFFECT OF COLLEGE MANAGEMENT SYSTEM ON RELATIONSHIP BETWEEN VOCATIONAL EDUCATION POLICIES AND COLLEGE-ENTERPRISE PARTICIPATION FACTORS ON THE COLLEGE-ENTERPRISE COOPERATION IN ZHENG ZHOU CITY UNDER HENAN PROVINCE - Mingyang, Liu; Pruettikul, Sataporn; Moonmuang, Sukhum (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) To explore the component of the college enterprise cooperation of vocational colleges in Zhengzhou city under Henan Province; (2) To develop the model factors affecting colleges enterprise cooperation of vocational education policies, colleges enterprise participation and colleges management system factors in Zhengzhou city under Henan Province; and (3) To verify the mediating effect of colleges management system on the relationship between vocational education policies and enterprise participation on the colleges enterprise cooperation. This research was quantitative research which conducted a survey on teachers from 12 vocational colleges in Zhengzhou city, Henan Province. The sample size determined by G*power software, totaling 600 teachers. and used stratified random sampling method. Data collection by a 5 rating score questionnaires which validity of item between 0.60 - 1.00, reliability of each component between .80 - .99 and data analysis by CFA and SEM. The research results showed that: (1) The components of the colleges enterprise cooperation were 3 components namely: profitability, sustainability, and satisfaction. There were at high level among vocational college in Zhengzhou city, Henan province; (2) The model of factors affecting college enterprise cooperation fit well with empirical data. (DF=55、CMIN=136.33、CMIN/DF=2.479、GFI=0.967、CFI=0.971、RMSEA=0.050), The composite reliability (CR) value of model was between .75-.81, validity of Model (AVE) was between .50-.52; and (3) The vocational education policies and enterprise participation had positive direct effect and indirect effect on colleges enterprise cooperation via colleges management system with statistically significance (p<.05). The colleges management system was mediator and could reduce effect on the relationship between vocational education policies and enterprise participation on the colleges enterprise cooperation.